Accelerated tumour metastasis due to interferon‐γ receptor‐mediated dissociation of perivascular cells from blood vessels. Issue 3 (25th May 2017) - Ni, Chen; Ma, Pan; Qu, Liwei; Wu, Fan; Hao, Junfeng; Wang, Ruirui; Lu, Yu; Yang, Wei; Erben, Ulrike; Qin, Zhihai
Abstract: Angiostasis mediated by interferon (IFN)‐γ is a key mechanism of anti‐tumour immunity; however, the effect of IFN‐γ on host vascular endothelial growth factor A (VEGFA)‐expressing cells during tumour progression is still elusive. Here, we developed transgenic mice with IFN‐γ receptor (IFNγR) expression under control of the Vegfa promoter (V‐γR). In these mice, the IFN‐γ responsiveness of VEGFA‐expressing cells led to dramatic growth suppression of transplanted lung carcinoma cells. Surprisingly, increased mortality and tumour metastasis were observed in the tumour‐bearing V‐γR mice, in comparison with the control wild‐type and IFNγR‐deficient mice. Further study showed that perivascular cells were VEGFA‐expressing cells and potential IFN‐γ targets. In vivo, tumour vascular perfusion and pericyte association with blood vessels were massively disrupted in V‐γR mice. In vitro, IFN‐γ inhibited transforming growth factor‐β signalling by upregulating SMAD7, and therefore downregulated N‐cadherin expression in pericytes. Importantly, IFN‐γ neutralization in vivo with a monoclonal antibody reduced tumour metastasis. Together, the results suggest that IFNγR‐mediated dissociation of perivascular cells from blood vessels contributes to the acceleration of tumour metastasis. Thus, the inhibition of tumour growth via IFN‐γ‐induced angiostasis might also accelerate tumour metastasis. Copyright © 2017 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.